ANGIOTENSIN I-CONVERTING ENZYME INHIBITORY ACTIVITY, TOTAL PHENOLIC AND FLAVONOID CONTENT OF EXTRACT AND FRACTION OF JAM FRUIT LEAVES (MUNTINGIA CALABURA L.) - Lasboi, Eka; Rissyelly, Rissyelly; Katrin, Katrin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Objective: Hypertension is one of the most common chronic diseases. Inhibitory activity of angiotensin I-converting enzyme (ACE) is effective on giving hypotensive effect. Jamfruit leaf (Muntingia calabura L.) was reported to have an excellent hypotensive effect. This research was aimed to test in the manner of in vitro the inhibitory activity of ACE. Methods: This research used ACE kit-WST, total phenolic content, and total flavonoid from jam fruit leaf ethanol extract, hexane, ethyl acetate, and butanol fraction. Results: The result showed that Jamfruit leaf extract had ACE inhibitory activity and the most active fraction was ethyl acetate fraction. Inhibitory concentration 50% value of the most active fraction, ethyl acetate fraction was 0.63 Î¼g/mL. Ethyl acetate fraction also provides most flavonoid and phenolic content with a value of 10.91 mg/g extract quercetin equivalent and 74.90 mg/g extract gallic acid equivalent. Conclusions: Ethyl acetate fraction of jam fruit leaf had most flavonoid, phenolic compound, and ACE inhibitory activity.